MicroRNA-155 Deficiency Attenuates Liver Steatosis and Fibrosis without Reducing Inflammation in a Mouse Model of Steatohepatitis - Csak, Timea (PLoS One, 2015)
BACKGROUND & AIM: MicroRNAs (miRs) regulate hepatic steatosis, inflammation and fibrosis. Fibrosis is the consequence of chronic tissue damage and inflammation. We hypothesized that deficiency of miR-155, a master regulator of inflammation, attenuates steatohepatitis and fibrosis. METHODS: Wild type (WT) and miR-155-deficient (KO) mice were fed methionine-choline-deficient (MCD) or -supplemented (MCS) control diet for 5 weeks. Liver injury, inflammation, steatosis and fibrosis were assessed. RESULTS: MCD diet resulted in steatohepatitis and increased miR-155 expression in total liver, hepatocytes and Kupffer cells. Steatosis and expression of genes involved in fatty acid metabolism were attenuated in miR-155 KO mice after MCD feeding. In contrast, miR-155 deficiency failed to attenuate inflammatory cell infiltration, nuclear factor κ beta (NF-κB) activation and enhanced the expression of the pro-inflammatory cytokines tumor necrosis factor alpha (TNFα) and monocyte chemoattractant protein-1 (MCP1) in MCD diet-fed mice. We found a significant attenuation of apoptosis (cleaved caspase-3) and reduction in collagen and α smooth muscle actin (αSMA) levels in miR-155 KO mice compared to WTs on MCD diet. In addition, we found attenuation of platelet derived growth factor (PDGF), a pro-fibrotic cytokine; SMAD family member 3 (Smad3), a protein involved in transforming growth factor-β (TGFβ) signal transduction and vimentin, a mesenchymal marker and indirect indicator of epithelial-to-mesenchymal transition (EMT) in miR-155 KO mice. Nuclear binding of CCAAT enhancer binding protein β (C/EBPβ) a miR-155 target involved in EMT was significantly increased in miR-155 KO compared to WT mice. CONCLUSIONS: Our novel data demonstrate that miR-155 deficiency can reduce steatosis and fibrosis without decreasing inflammation in steatohepatitis.